Aeromagnetic exploration over the East Antarctic Ice Sheet: a new view of the Wilkes Subglacial Basin - F. FERRACCIOLI; T. JORDAN; H. CORR; ARMADILLO, EGIDIO; BOZZO, EMANUELE (Tectonophysics, 2009)
The Wilkes Subglacial Basin represents an approximately 1400 km-long and up to 600 km wide subglacial depression, buried beneath the over 3 km-thick East Antarctic Ice Sheet. Contrasting models, including rift models and flexural models, have been previously put forward to explain the tectonic origin of this enigmatic basin, which is located in the largely unexplored hinterland of the Transantarctic Mountains. A major aerogeophysical survey was flown during the 2005–06 austral summer to explore the Wilkes Subglacial Basin. Our new airborne radar dataset reveals that the Wilkes Subglacial Basin contains several subglacial basins, which are considerably deeper than previously mapped. Major aeromagnetic lineaments are detected from total field, pseudo-gravity, tilt derivative and Euler Deconvolution maps. These aeromagnetic lineaments reveal that the Wilkes Subglacial Basin and its sub-basins are structurally controlled. Comparison between aeromagnetic signatures over the Wilkes Subglacial Basin region and the Cordillera in North America, suggests that the basin contains a former broad backarc basin and fold-and-thrust belts, forming the transition between a Precambrian craton and the Ross Orogen. The eastern margin of the Wilkes Subglacial Basin is imposed upon the Prince Albert Fault System and the Priestley Fault. These faults may have been reactivated in the Cenozoic, as major strike–slip faults. The western margin of the Wilkes Subglacial Basin is located along the southern extension of the Precambrian-age Mertz Shear Zone and marks the edge of the Terre Adélie Craton. High-frequency aeromagnetic anomalies in the Wilkes Subglacial Basin image large volumes of Jurassic tholeiites, which were intruded into and extruded over Beacon sediments in a possible rift setting. Depth-estimates of magnetic anomaly sources and forward modelling indicate that major Cretaceous and Cenozoic rift basins with thick sedimentary infill, comparable to the deep Ross Sea Rift basins, are however unlikely beneath this part of the ...